Language Options in Food Product Advertising on YouTube - Fira Maghfiro Tunnisa (Journal of Digital Business and Data Science, 2024)
The purpose of this study is to describe the form of language choice in speech events in advertisements for food products on YouTube and to describe the factors that determine the choice of language in speech events in advertisements for food products on YouTube.This research uses a qualitative descriptive research type. This research was carried out from December 2020 to May 2021. The data taken in this study were the utterances of commercial stars in 20 advertisements for food products on YouTube videos which were transcribed in written text. The data source used is food product advertisements on YouTube. The data collection technique used in this study is the note-taking technique. The data validation technique uses triangulation techniques. The method used in analyzing the data is the intralingual and extralingual equivalent methods. In food product advertisements on YouTube, 9 data were found using single language variations. Code switching data was found to be 2 codes. Then the ads using code mixing totaled 9 data with the form of words and phrases.